Digital Halal Assurance: A Comparison of Consumer Protection in Indonesia and Malaysia - Karimatul Khasanah; Ainul Yaqin; Neng Vivie Nurfauziah Rukmini (UIN Siber Syekh Nurjati Cirebon, 2026)
The digitalization of commerce has transformed the distribution of halal products and created new challenges for consumer protection in digital marketplaces. This article aims to comparatively analyze how Indonesia and Malaysia regulate and implement halal consumer protection in e-commerce, particularly regarding platform verification, consumer information rights, and access to dispute resolution. This study employs a normative-comparative legal method supported by statutory, conceptual, and comparative approaches. The analysis examines primary legal materials, including Indonesia’s Halal Product Assurance Law and Malaysia’s Trade Descriptions Act 2011, as well as secondary legal materials and semi-structured interviews with representatives of BPJPH Indonesia and JAKIM Malaysia. The findings show that Indonesia has a strong de jure halal assurance framework, but its implementation in digital marketplaces remains weak due to unclear platform liability, the absence of mandatory integration with BPJPH’s SIHALAL database, and the limited adaptability of consumer dispute mechanisms. In contrast, Malaysia provides a more integrated model by defining halal as a trade description, strengthening JAKIM’s certification authority, supporting platform-based verification through MyEHalal and Halal Lane initiatives, and providing accessible redress through the Tribunal for Consumer Claims. This study contributes to the development of digital halal governance by emphasizing the need for platform due diligence, integrated verification systems, and adaptive dispute resolution mechanisms to strengthen halal consumer protection in Indonesia.